Hydromastodon sallesi, new genus and new species of Atalophlebiinae (Insecta: Ephemeroptera: Leptophlebiidae) from West and North of Brazil, and notes on systematics of Hermanella group - Polegatto, C. M.; Batista, J. D. (Zootaxa, 2007)
The genus Hydromastodon is described here with a new species H. sallesi, and a new combination: Hydromastodon (=Hydrosmilodon) mikei (Thomas & Boutonnet 2004). H. sallesi was described based on nymphs from Pindaíba Stream, near Nova Xavantina, State of Mato Grosso, and from Bem Querer Stream, State of Roraima, Brazil. Hydromastodon can be distinguished from other genera of the Hermanella group by presence of posterolateral spines on abdominal segments 6 or 7 to 9, tarsal claws with subequal denticles in two separate rows, without large subapical denticle, and clavate setae on legs. Hydromastodon seems to be closely related to Hydrosmilodon and Leentvaaria.